Vernacular reviews as a form of co-consumption: The user-generated review videos on YouTube - Jaakkola, Maarit (MedieKultur: Journal of media and communication research, 2018)
Reviews of arts and culture are typically focused on legitimate forms of art rather than popular and consumer culture. Looking beyond such institutionalized reviews, this article inquires into the online-native, bottom-up forms of reviewing. The aim is to identify user-generated reviews of popular cultural objects, defined through the user reviewers’ position as cultural consumers and the size of their audiences. The objects of study are YouTube channels that include a regular output of review videos. First, the 5,000 most-subscribed channels are analysed to identify content creators who establish a relationship to cultural objects. Second, types of reviewing are identified, and the methods and boundaries of ‘vernacular reviewing’ are discussed. User-generated reviewing on YouTube presents a meta-practice related to cultural objects for young audiences that is marked by the use of hybrid genres, humour, irony and the idea of co-consuming, reflected in the concept of intramediation